PERANCANGAN SISTEM INFORMASI HELPDESK PADA FAKULTAS ILMU KOMPUTER UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Fadhil Wintan Hukama Maharana, (2021)
The development of information technology makes information technology become the main facility for various activities faculty of computer science, Universitas Pembangunan Nasional Veteran Jakarta already take advantage of information technology as their facilities to make students do various activities easier. This research was conducted for the development of information technology for question-and-answer media as a service medium that was previously not yet computerized so that if internal and external parties have problems or questions, they must contact related parties or technicians that can help them. The development of this information technology uses the SDLC (system development life cycling) method with the waterfall strategy where the process of development starting from analysis, design, coding & testing, implementation, and maintenance. The development of this web-based information technology uses ReactJS which is an open-source JavaScript library and NodeJS as a server-side program that connect with PorstgreSQL. This research will produce a helpdesk information technology that can help faculty of computer science, Universitas Pembangunan Nasional Veteran Jakarta gives a better services.